Formulation Development and Evaluation of Transferosomal Gel Using Trifarotene - Prajapati, Anuradha; Tandel, Muskan; Narkhede, Sachin B; Desai, Neha; Luhar, Shailesh; Narkhede, Kantilal (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Trifarotene (TFT), a retinoid commonly used for acne treatment, suffers from poor water solubility, limiting its effectiveness and increasing the risk of side effects. Enhancing its bioavailability and providing sustained drug release could improve therapeutic outcomes while reducing side effects. Objectives: The study aimed to develop and optimize a transferosomal gel formulation of Trifarotene to enhance drug availability at the target site, achieve sustained release, and minimize side effects. Materials and Methods: A 3² factorial design was used to optimize the transferosome formulation, prepared via the thin lipid film hydration method using a rotary vacuum evaporator. The study varied the type and concentration of edge activators and incorporated phospholipids and surfactants into the formulation. The optimized formulation was then converted into a gel and evaluated based on particle size, Polydispersity Index (PDI), zeta potential, entrapment efficiency, and in vitro drug release percentage. Additional evaluations included excipient compatibility via Differential Scanning Calorimetry (DSC), surface morphology using Scanning Electron Microscopy (SEM), and the gel's physical characteristics (pH, viscosity, extrudability, Spreadability, and skin irritation potential). Stability studies were conducted as per ICH guidelines. Results: The optimized transferosomal gel showed favourable in vitro drug release with significant improvement in bioavailability. Independent variables, including edge activator concentration, had a statistically significant impact on the formulation's characteristics (p<0.005). Excipient compatibility was confirmed via DSC, and SEM analysis revealed suitable vesicle morphology. The gel was found to be stable, safe, and compatible with skin layers at a low dose, with no signs of skin irritation. Conclusion: The optimized Trifarotene transferosomal gel formulation enhanced drug delivery, improved skin penetration, and provided sustained release with minimal side effects, showing promise for safe and effective acne treatment.
Keywords: Acne; Thin lipid film hydration; Transferosomal gel; Transferosome; Trifarotene.